When Certification Matters More Than Productivity: Geographical Indications and the Social Construction of Coffee Prices Among Smallholder Farmers in Rural Indonesia - Riantri Barus; Hilda Fitrah Nasution; M. Jufri (Universitas Pattimura, 2026)
This article examines how Geographical Indication (GI) certification reshapes coffee price formation and smallholder farmers’ income beyond conventional productivity-based explanations. Challenging dominant agricultural development perspectives that associate income growth primarily with yield improvement, the study addresses a paradox among Arabica coffee farmers in Sipirok, rural Indonesia: certified farmers exhibit lower productivity and higher production costs, yet achieve significantly higher incomes. Using a comparative quantitative design with sociological interpretation, data were collected from 61 GI-certified and 29 non-certified farmers. Annual cash flow analysis and independent sample t-tests were applied to compare production levels, costs, prices, and income. The results indicate that GI-certified farmers incur substantially higher costs, mainly due to organic inputs and strict harvesting standards, and obtain lower yields, but receive coffee prices approximately 2.5 times higher than those of non-certified farmers, leading to statistically higher incomes. These findings demonstrate that price, rather than productivity, constitutes the primary mechanism of income differentiation. Drawing on economic and rural sociology, the study conceptualizes GI certification as a market institution that socially constructs prices through legitimacy, symbolic value, and consumer trust linked to origin and quality. The article contributes empirical evidence from Indonesia on how symbolic valuation reshapes agrarian livelihoods and generates new forms of market dependence.